Early predictors of mortality for moderate to severely ill patients with Covid-19 in Erbil city - Taha Khudhur Ahmed; Halgurd Fathulla Ahmed; Haval Faris Mohammed (Advanced Medical Journal)
Background & Objectives: COVID-19 disease represents a major burden on national health institutes. The aim of study is to figure out the parameters that can predict the mortality in moderate to severely ill Covid-19patients. That enable us to predict the course of the disease and reduce the mortality of Covid-19 patients.